The good living in Ecuador: Political Marketing or Project in Dispute? A Dialogue with Alberto Acosta - Blanca Fernández; Liliana Pardo; Katherine Salamanca (Íconos)
The good living in Ecuador: Political Marketing or Project in Dispute? A Dialogue with Alberto Acosta